Sobre a aquisição da Fonologia do Português Europeu como L1: caminhos por trilhar - Costa, Teresa; Amorim, Clara; Ramalho, Ana Margarida (Revista da Associação Portuguesa de Linguística, 2022)
This text presents a set of reflections on the state of the art regarding phonological acquisition in European Portuguese as L1. Taking the existing research accomplishments as its starting point, the discussion presented here will focus on what still needs to be done and known in different domains: regarding the construction, validation and availability of corpora and tools for phonological assessment; in the study of typical and atypical development; in the relationships between research and clinical and pedagogical intervention. Among the paths to be followed, emphasis will be placed on the need to instill multidisciplinary and multimodal approaches in phonological acquisition research, combining data from production, perception and metaphonological processing